Пусть искры слов зажгут сердца: сборник стихов / Галина Дурова - Дурова Галина Михайловна (1999)
Экземпляры: ЦБ (2004) / Инвентарный номер: 36668 / Цена: 30.00 / Сис.шифр: 84(2Рос=Удм) / Авт.знак: Д 84 / ГРНТИ: 17.82.10 /